Research Progress on Traditional Chinese Medicine Treatment of Recurrent Oral Ulcers in Children - Lv, Xiaoying; Guo, Yaxiong (Journal of Contemporary Medical Practice, 2025)
Objective: To analyze and discuss the treatment of recurrent oral ulcers with traditional Chinese medicine (TCM), in order to provide a reference for the treatment of recurrent oral ulcers and other related oral diseases with TCM in the future. Methods: The key words “recurrent oral ulcers in children” or “recurrent aphthous ulcers in children” and the Chinese medical names “aphthous ulcers”, “aphthous ulcers”, “mouth ulcer”, “mouth erosion”, etc., and secondary searches with “Chinese medicine”, “combination of Chinese and Western medicine”, etc. were performed. A secondary search with “Chinese medicine” and “combination of Chinese and Western medicine” was performed to screen the eligible literature for review. Results: More than 30 articles were retrieved from the literature on the treatment of recurrent oral ulcers by TCM from 2014 to 2024. Conclusion: TCM recurrent oral ulcers have a variety of modalities, with the advantages of high cure rate and low recurrence rate.